2000
DOI: 10.1207/s15327914nc381_5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary, Drinking, and Smoking Habits on the Prognosis of Gastric Cancer

Abstract: Although it has been clarified that dietary, drinking, and smoking habits contribute to the onset of gastric cancer, little is known about their impact on prognosis of gastric cancer. To examine this question, a prognostic analysis was conducted using data from Aichi Cancer Center Research Institute and Hospital. From January 1988 to December 1994, information on 877 gastric cancer patients (578 men and 299 women) regarding habitual smoking and drinking, food consumption, histological grade, and clinical stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 47 publications
3
40
0
Order By: Relevance
“…In our study group, 30% of the women were current smokers and they had a shorter survival after ovarian cancer compared with nonsmokers. This is in line with results on other cancer types (10-13), and although the exact mechanism is unknown, it has been suggested that tobaccosmoke carcinogens may induce a more aggressive cancer type (e.g., inducing p53 mutations), and that smoking may have a negative effect on the immune system, making it less capable of destroying the cancer cells (10,26). Smoking has also been shown to be associated with other unhealthy lifestyle habits (27), which, in themselves may have a negative effect on survival.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study group, 30% of the women were current smokers and they had a shorter survival after ovarian cancer compared with nonsmokers. This is in line with results on other cancer types (10-13), and although the exact mechanism is unknown, it has been suggested that tobaccosmoke carcinogens may induce a more aggressive cancer type (e.g., inducing p53 mutations), and that smoking may have a negative effect on the immune system, making it less capable of destroying the cancer cells (10,26). Smoking has also been shown to be associated with other unhealthy lifestyle habits (27), which, in themselves may have a negative effect on survival.…”
Section: Discussionsupporting
confidence: 89%
“…Only overweight was a significant prognostic factor, as too few cases were ever smokers to make any conclusions on the effect of smoking on survival. Other studies have shown that smoking has a negative prognostic effect on survival in patients diagnosed with cancer in the lung, breast, prostate, and stomach (10)(11)(12)(13). Although smoking has not been found to influence ovarian cancer mortality (14), it is unknown whether smoking is associated with survival after ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…17). However, in a Japanese study, current or ever-habitual drinking did not significantly increase mortality HRs (16).…”
Section: Introductionmentioning
confidence: 75%
“…In a Japanese study with 877 patients with gastric cancer, the risk ratio for death was 2.53 [95% confidence interval (CI), 1.22-5.29] for habitual smokers, and an inverse dose-response relationship was found between ever smoking and gastric cancer patient survival (16). On the other hand, in a study with 14,578 Korean men, Park and colleagues identified that patients with gastric cancer with a prediagnosis smoking history had better survival rates than nonsmokers in multivariateadjusted analyses (HR for mortality, 0.83; 95% CI, 0.72-0.95; ref.…”
Section: Introductionmentioning
confidence: 99%
“…First-generation migrants from high-incidence countries to low-incidence countries sustain the risk rate of their native country, whereas subsequent generations acquire the risk rate of their new environment [5, 6]. A diet rich in fruits and vegetables may be associated with a reduced risk of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%